Rancang Bangun Jaringan Hotspot Menggunakan LINUX ClearOS Dengan Konsep Security Gateway - Arie Gunawan; Rosyidah Rahmah; Agus Iskandar (JTIM : Jurnal Teknologi Informasi dan Multimedia, 2023)
Hotspot checks certain places (usually public places) that have Internet services with wireless LAN technology, like universities, shopping malls, squares, libraries, restaurants or airports. Internet services like these are available for a fee and free. a sensible approach is required to manage server protection, namely by protecting the prevailing network. Where there's level of security to secure access and access rights to existing hotspots. A gateway may be a tool that's wont to connect a network to at least one or more computer networks that use different communication protocols, so information from an system is provided to other computer networks that use different protocols. to form this method, the author uses Linux ClearOS for the protection concept. this method is applied to the case study of PT. XYZ, which uses the hotspot. The author describes how security systems are installed and built on network servers, and describes gateways as network infrastructure. so the present hotspot medium can maximize its working system by using Linux software, which is another hotspot.